Explosives: Effectiveness in dragline blasting in surface coal mines - Sharma S.K. (My University, 2025)
The article discusses the problem situations in overburden blasting of dragline benches and proposes a methodology for successful and effective blasting for dragline benches. The effectiveness of these blasts depends on the successful application of the explosive energy. Effectiveness of the explosive use determines the success of the deployment of the draglines, its productivity, and its life and safety.